Pelatihan Dan Pendampingan Perhitungan Harga Pokok Produksi Bagi Pelaku UMKM Di Desa Ngoro-Oro Gunungkidul - Nafiati, Lu’lu’; Herman Yuliansyah; Surahma Asti Mulasari; Fatwa Tentama; Sulistyawati; Tri Wahyuni Sukesi (Jurnal Pengabdian Pada Masyarakat, 2022)
TRAINING AND ASSISTANCE OF COST OF PRODUCTION CALCULATION FOR MSME ENTERPRISES IN NGORO-ORO GUNUNGKIDUL; Ngoro-oro Village is a village in Gunungkidul Regency that has the potential to be developed into a tourist village that is able to encourage the formation of a good environment for micro, small and medium enterprises (MSMEs) in this village. On the other hand, the development of MSMEs in the area is still very limited. The purpose of this program is to provide training and assistance to improve the ability to calculate the cost of production for MSME in Ngoro-oro Village. The target of this program are the MSME in the Ngoro-Oro village. MSMEs in Ngoro-oro Village are managed into a community that is part of the UKM “Bangkit”. The method used is in the form of training and direct practice of calculating the cost of production of processed products by MSME. The results of this assistance show that on average the participants are able to calculate the cost of production for each product produced by MSMEs. The benefits of this training can help MSME design their production processes and can find production results and project the profits they will get from the beginning, so that their business can continue to grow.Cost of Production